Paleovegetation in West Africa for 18.000 B.P. and 8.500 B.P. - D. Anhuf (Eiszeitalter und Gegenwart, 1997)
The investigations were concentrated on the reconstruction of former vegetation patterns tor the Sudanian and Guinean savannas as well as tropical semi-evergreen and evergreen rainforests. A numher of research projects concerning changes in the vegetation cover have shown that even tropical regions have been effected by the enormous climatic oscillations of the last 20,000 years. The problem linked to the judgement of a changing vegetation is the increasing effect of human influence on the appearenee of the West African vegetation cover. Thus, all investigations of the temporal change in tropical ecosystems are confronted with the fact that areas which have not been influenced by man can rarely be found. The primary question is which formations of vegetation may allow us to draw conclusions applicable to a nearly natural vegetation. A first step is the estimation of potential forest communities under recent climatic conditions. The derivation of the paleovegetation of West Africa was based on varied published information concerning paleoclimate and paleovegetation. This information is bound to the subjects of archaeology, geomorphology, dendrochronology, palynology, deep-sea-core and isotope analysis. By derivation of the numeric relations between natural vegetation and climate under recent conditions, according models of analogous vegetation climate of palcoclnnatic conditions could be drawn. Presented are paleovegetation maps of West Africa for 18.000 B.P. (glacial climatic pessimum) and 8.500 B.P. (postglacial climatic optimum).